Analysis of the Continuance Intention to Use Telemedicine Applications Mediated by Customer Satisfaction - Rahmi, Indira Nisa; Astuti, Miguna; Manggabarani, Alfatih Sikki (Yayasan Sinergi Kawula Muda, 2026)
This study aims to analyze the factors influencing continuance intention to use telemedicine applications in Indonesia by integrating perceived usefulness, perceived ease of use, perceived enjoyment, trust, and customer satisfaction as a mediating variable within an extended Technology Acceptance Model (TAM). A quantitative research design was applied using an online questionnaire distributed to 400 telemedicine users in DKI Jakarta, consisting of respondents aged 18–55 years with a gender distribution of 54% female and 46% male. The extension of TAM in this study clarifies how hedonic (perceived enjoyment) and trust-based components enhance the explanatory power of traditional TAM constructs by capturing both utilitarian and affective determinants of post-adoption behavior an aspect often overlooked in prior telemedicine research. Results obtained through Structural Equation Modelin –Partial Least Squares (SEM-PLS) using SmartPLS 4.0 show that perceived usefulness, perceived enjoyment, and trust significantly influence continuance intention both directly and indirectly through customer satisfaction, while perceived ease of use has no significant effect. Customer satisfaction is confirmed as a central mediating variable, reinforcing the long-term use of telemedicine services. These findings align with global digital health priorities and provide practical insights for healthcare policymakers and telemedicine developers in improving user retention and optimizing post-adoption engagement in Indonesia’s digital healthcare ecosystem.